Teaching Critical Discourse Analysis of Sociocognitive Approach to EFL Learners through Corpus-based Analysis - Samsi, Yogi Setia; Lukmana, Iwa; Sudana, Dadang (ELT in Focus, 2020)
Many studies have been researching critical discourse analysis, henceforth CDA, in analyzing a numerous contexts, nevertheless, those studies still have lack of contributions such as in pedagogical aspects and lack of incorporations with specialized technology such as corpus tool. However, this study intended to fill a gap that qualitatively aimed to explore on how teaching CDA focusing on sociocognitive approach through corpus analysis and to know learners’ responses about their experience. Then, this study concerns to three elements: corpus based approach, CDA approach, and pedagogical approach. The target of participants were undergraduate students of university in Karawang, Indonesia. It was randomly participated from higher semester, 7th semester, had been studying linguistics and learning media. The study ran for one month and included two training sessions for learners on how to use concordance software in analyzing words, phrases, concordance line, frequencies, and collocations in order to get sociocognitive which specialized by only microstructure couched by Van Dijk (2008). The corpus were made from 2 different newspaper with a specific issue contained a big data. The main findings showed that the participants can be able to use a concordance software independently as it seemed very excited in the exercise. It indicated successful way that students eventually can criticize some discoures through corpus analysis that corroborated by the training and the learners’ responses. However, the further study requires to deepen and incorporate with other approaches such as systemic functional linguistics to strengthen the analysis.